Ultrasound assessment of carotid artery atherosclerosis and endothelial function in young and middle-aged men with coronary heart disease - T. V. Balakhonova; S. G. Kozlov; Kh. A. Makhmudova; M. I. Tripoten; A. A. Lyakishev; V. V. Kukharchuk (Кардиоваскулярная терапия и профилактика)
Aim. Ultrasound assessment of carotid artery atherosclerosis and endothelial function in young and middle-aged men with coronary heart disease (CHD).Material and methods. The study included 78 men aged 28-50 years: 49 CHD patients with angiography-verified coronary artery atherosclerosis and 29 controls (control group, CG), without clinical atherosclerosis manifestations. All participants underwent a standard carotid artery (CA) ultrasound. Brachial artery flow-dependent vasodilatation (FDVD) was assessed in reactive hyperemia test.Results. Among CHD patients, intima-media thickness (IMT) for common CA (0,88±0,23 mm) was significantly higher than in CG individuals (0,76±0,18 mm; р=0,01). Atherosclerotic plaques in common CA were observed in 91,8% of the CHD patients and 27,6% of controls (р<0,001). Multiple plaques were observed in 80% and 14%, respectively (р<0,001). Average brachial artery FDVD (5,8±2,2%) was significantly higher than that in CHD patients (4,5±2,8%; р=0,03).Conclusion. No significant differences in the prevalence of normal FDVD were observed between two groups. Increased IMT and multiple atherosclerotic plaques in common CA were associated with higher CHD risk in young and middle-aged men.